Jenis-Jenis Kelelawar(Chiroptera) di Kawasan Hutan Tanjung Datok Kecamatan Paloh Kabupaten Sambas - Ari Hepi Yanti, Dino Riano, Tri Rima Setyawati (Jurnal Protobiont, 2016)
Bats is on of Order Chiroptera which have the highest species richness in tropical forests compared to other mammals. This research aims to identify the species of bats in the Area of Tanjung Datok Forest. Data were collected from September to October 2015. Bats were collected directly from three stations using the trappingmethodmist nets. As many as 3 pieces of mist nets were mounted at three points in each station. Theidentification was carried out in the Laboratory of Zoology Department of Biology, Faculty of Mathematics and Natural Sciences,Tanjungpura University Pontianak. The result showed that were 2 families and 4 species of bats found in the area of Tanjung Datok Forest. three species from family Pteropodidae Cynopterus brachiotis, Dycopterus spadiceus, and Penthetor lucasii,while one species from family Emballonuridae wasEmballonura electo.